Digital Behavior in Organizations: Employee–Customer Interaction in Platform Ecosystems - Suharyanto Suharyanto (PT. Hafasy Dwi Nawasena, 2026)
The accelerating digitalization of organizational environments has fundamentally reshaped how employees interact with customers, particularly within platform-mediated ecosystems. This study examines the nature, determinants, and consequences of digital behavior in organizations, with a specific focus on employee customer interaction dynamics within platform ecosystems. Drawing on a systematic synthesis of empirical and conceptual literature published between 2021 and 2026, this article develops an integrated research framework that identifies four key antecedents employee digital competence, organizational transformation support, AI-enabled automation tools, and digital workspace design and traces their effects on interaction quality, customer engagement, and organizational performance. The findings indicate that platform ecosystems serve as critical mediating contexts in which employee digital behaviors are enacted, amplified, or constrained. Value co-creation, ecosystem fluidity, and governance mechanisms emerge as pivotal moderating factors. The study contributes an integrative framework to the literature on digital organizational behavior, interactive marketing, and platform management, and offers practical guidance for organizations seeking to optimize digital touchpoints in customer service delivery.